Social Networks and Knowledge Sharing in Communities of Practice: A Developing Societies' Perspective - Maryam Tabatabaee, Ravishankar Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article explores the idea of using social networks for knowledge transfer and sharing in the context of Communities of Practice (CoPs). The current Covid-19 pandemic has made such research crucial to study the benefits of digital platforms. The notion of a knowledge ba and its implementation over a digital platform is a cybernetic one with voluminous prior research. This article briefly reviews the extant literature on social media and knowledge sharing in order to prescribe a research agenda. The specific research question investigates if and how knowledge sharing can take place across virtual communities and digital platforms to bridge inequalities through growth and development opportunities.